Study of Microbial Degradation of Bioplastic Sheets Prepared by Using Natural Polymer-Corn Starch - Sandhya Kadam; Vaishnavi Kharade; Priti Indalkar; Padmarani Patil; Pranali Patil; Pratibha Patil; Vidya Patil (The Bioscan, 2025)
Interest in creating eco-friendly substitutes like bioplastics has increased as a result of growing environmental concerns about non-biodegradable plastics. The microbial breakdown of bioplastic sheets made with natural polymers, such as corn starch, is investigated in the present research work. Bioplastic sheets made from corn starch, a renewable and biodegradable material, were examined under controlled microbiological experiments for their physical characteristics, biodegradability, and structural integrity. The corn starch bioplastic can be added with functional ingredients, for instance, antimicrobial and antioxidant agents, or color and flavor ingredients. The use of glycerol as a plasticizer gives flexibility to sheets and modifies the physical characteristics of starch-based sheets and coatings. Sheets prepared with starch are colorless and odorless, and the diameter of the sheets is 7.5 cm. Prepared sheets without homogenizer (white vinegar) are uneven and those with homogenizer (white vinegar) are even. Also performed SEM (scanning electron microscopy) to check the surface of bioplastic sheets. Microorganisms degrade natural polymers and synthetic polymers through a process called biodegradation. The study investigates the microbial degradation of bioplastic sheets made from natural polymers like corn starch. For this study, soil samples were selected as a source of potential microbes having degradation ability naturally. After the biodegradation study, bioplastic sheets were tested for structural integrity and physical properties under controlled experimental conditions. Results showed significant microbial degradation of bioplastic sheets and their potential as sustainable substitutes for traditional plastics. The significance of bioplastics derived from natural polymers in combating plastic pollution and advancing a circular bioeconomy is highlighted by the current research study.